Transformasi Kawasan Hutan Menjadi Destinasi Wisata dan Keberlanjutan Lingkungan di Nature Park (NAPA) Forest Palangka Raya - Mutia Zakia Rahma; Alfira Damayanti; Jessica Amelia (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The transformation of forest areas into tourism destinations has emerged as a strategic approach to promoting sustainable development through the integration of environmental conservation, educational value, and community economic empowerment. This article examines the conversion of forest landscapes into tourism attractions and its implications for environmental sustainability in Nature Park (NAPA) Forest, Palangka Raya. A descriptive qualitative approach was employed, utilizing interviews, observations, and documentation as the primary data collection techniques. The findings indicate that the transformation has generated positive environmental outcomes, reflected in the preservation of jelutung tree vegetation, the establishment of a favorable microclimate, and the maintenance of peatland hydrological functions. From the perspective of environmental carrying capacity, tourism activities remain within acceptable ecological limits, although increasing visitor numbers may create future environmental pressures. Viewed through the lens of ecotourism theory, NAPA Forest demonstrates the implementation of key ecotourism principles, including conservation, environmental education, and local economic empowerment. The long-term sustainability of the area depends on consistent management practices and strengthened collaboration among site managers, government institutions, and conservation organizations to ensure a balance between tourism utilization and environmental preservation.